Validation of electromagnetic physics models and electron range in Geant4 Brachytherapy application - A. Albqoor; E. Ababneh; S. Okoor; I. Zahran (Nuclear Engineering and Technology, 2023)
The mechanics underlying photon and electron interactions was validated using our developed Brachytherapy computer code for high Dose Rate (HDR). By comparing the photon cross-section utilizing multiple physics libraries in the developed code, the results were benchmarked against experimental and theoretical findings. Klein-Nishina and experimental cross-section results were in good agreement with the Livermore library results. For two therapeutically relevant materials, the first scattered electron range was measured within 1 mm and 2 mm, which has significant implications for the interpretation of the kernel dose spikes observed in previous research.